Relationship between intelligence and socio-economic competences in children and adolescents - de Cassia Nakano, Tatiana (2019)
The combination of cognitive and socioemotional competencies has been a focus of interest in the scientific literature given the impact of both on educational outcomes, the labor market and social behavior. In light of this situation, the present research aimed to investigate the relationship between cognitive and socioemotional competencies. The study enrolled 362 Brazilian students from the 3rd year (n = 168) and the 5th year (n = 194) of elementary school, aged 8 to 15 years (M = 10.3 years, SD = 1.33, 180 females). Participants answered five sub-tests of intelligence (verbal, abstract, numerical, spatial and logical) and a scale for the evaluation of socioemotional abilities (composed of the factors of openness to experiences, conscientiousness, extraversion, agreeableness, control locus and emotional stability). The results showed significant correlations between the six factors that compose the socioemotional competencies and the total score in the intelligence measure, confirming the importance of both being stimulated in different contexts.